Lost son : an American family trapped inside the FBI's secret wars - Forrest, Brett (Little, Brown and Company, 2023)
"When a young American named Billy Reilly vanished into Russia's war with Ukraine, his parents embarked on a desperate search for answers. Was their son's disappearance connected to his mysterious work for the FBI, or was it a personal quest gone wrong? Only when Wall Street Journal reporter Brett Forrest embarks on his own investigation does a picture emerge: of the FBI's exploitation of US citizens through a secretive intelligence program, of a young man's lust for adventure within the world's conflicts, and the costs of a rising clash between Moscow and Washington"--Dust jacket flap.